Engineering Happiness : a New Approach for Building a Joyful Life. - Baucells, Manel, 1966- (University of California Press, 2012)
Manel Baucells and Rakesh Sarin have been conducting ground-breaking research on happiness for more than a decade, and in this book they distill their provocative findings into a lively, accessible guide for a wide audience of readers. Integrating their own research with the latest thinking in the behavioral and social sciences--including management science, psychology, and economics--they offer a new approach to the puzzle of happiness. Woven throughout with wisdom from the world's religions and literatures, Engineering Happiness has something to offer everyone--regardless of background, profess.